Whale sharks Rhincodon typus get cleaned by the blue‐streak cleaner wrasse Labroides dimidiatus and the moon wrasse Thalassoma lunare in the Philippines - Gonzalo Araujo; Joni A. Miranda; Harriet L. Allen; Jessica Labaja; Sally Snow; Alessandro Ponzo; Christine G. Legaspi (Journal of Fish Biology, 2020)
Cleaning interactions are essential for healthy marine ecosystem communities. This study reports the first documentation of the whale shark Rhincodon typus cleaning behaviour in the Indo‐West Pacific by two wrasse species, the blue‐streak cleaner wrasse Labroides dimidiatus and the moon wrasse Thalassoma lunare in Cebu, Philippines. This study documented 36 cleaning interactions with 14 individual whale sharks. The cleaning interactions appear opportunistic rather than targeted by the sharks, unlike that observed in other species of elasmobranchs. Further work should focus on understanding the drivers of these unique cleaning interactions.